Spontaneous spleen rupture in infectious mononucleosis – case report and return-to-play recommendations for paediatric patients - Wolski, Marek; Piasecki, Maciej; Kamiński, Andrzej (Pediatria Polska - Polish Journal of Paediatrics, 2022)
Significant enlargement of the spleen in the course of infectious mononucleosis (IM) may result in spontaneous rupture and life-threatening bleeding. Patients are advised about activity limitation; however, this is based on institution experience and local recommendations. What is important, recommendations for the subgroup of paediatric patients are lacking, and a significant portion of splenic ruptures occur outside the time window of the mentioned current return-to-play recommendations. The aim of this publication was to look closely at the problem of timing and prevention of spleen rupture in the context of IM. Based on clinical experience and retrospective analyses of cases previously published as well as the case report presented, the author proposes a set of recommendations for paediatricians.